The Effect of Visual Biofeedback Balance Training on Time to Stabilization and Kinetic Variables in Patients with Chronic Ankle Instability - Sungmin Kim; Jeheon Moon (Korea Institute of Sport Science, 2022)
PURPOSE This study aimed to analyze the dynamic posture stabilization and kinematic variables between visual feedback and Y-balance training groups during jump-landing. METHODS Thirty-eight male players (age: 22.6 ± 1.12 years, height: 175 ± 3.54 cm, weight: 65.5 ± 5.11 kg) were included in this study, and chronic ankle instability was checked using Cumberland Ankle Instability Tool (CAIT) and Balance Error Scoring System (BESS). They were randomly assigned to the Visual biofeedback (Training group: TG, n = 19) and Y-balance groups (Control group: CG, n = 19) for four weeks. TG performed balance training using the Biodex balance system (BBS) and CG performed training using the Y-balance system. During jump landing, time to stabilization (TTS), force plate (COP, GRF); joint angle and moment were collected and analyzed. All analyses were performed with SPSS 21.0, and Bonferroni was used for repeated measured ANOVA and post-hoc. RESULTS The results indicated that there was an interaction between TG and CG in terms of AP and ML directions of TTS (p < 0.05). AP/ML TTS of the TG for the post-test was smaller than that for CG (AP: p = 0.000; ML: p = 0.046). ML TTS of the TG for post-test was smaller than at pre-test (p = 0.041), and AP TTS of the CG for ankle joint moment (p < 0.05). There was an interaction between TG and CG in terms of dorsiflexion (DF) and plantarflexion (PF) of joint moment (p < 0.05). Ankle moment of the CG for post-test decreased than at pre-test (DF: p = 0.040, PF: p = 0.032), and ankle dorsiflexion moment of the CG for post-test was decreased than at pre-test (p = 0.046). CONCLUSIONS Balance ability was achieved more effectively through visual biofeedback training than Y-balance training. Therefore, we recommend balanced training with visual feedback on chronic ankle instability.